2013
DOI: 10.1016/s0254-6272(13)60103-x
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of periplaneta americana extract on intestinal mucosal barrier function in patients with sepsis

Abstract: The extract of periplaneta americana had protective effect on intestinal mucosal barrier and could improve the condition and prognosis in patients with sepsis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(44 citation statements)
references
References 6 publications
2
42
0
Order By: Relevance
“…Extracts of the American cockroach have been shown to protect against intestinal mucosal barrier dysfunction . Such extracts have been shown to not only inhibit the release of inflammatory mediators, as confirmed herein, but also to suppress immune responses .…”
Section: Resultssupporting
confidence: 61%
See 1 more Smart Citation
“…Extracts of the American cockroach have been shown to protect against intestinal mucosal barrier dysfunction . Such extracts have been shown to not only inhibit the release of inflammatory mediators, as confirmed herein, but also to suppress immune responses .…”
Section: Resultssupporting
confidence: 61%
“…Extracts of the American cockroach have been shown to protect against intestinal mucosal barrier dysfunction [15,16]. Such extracts have been shown to not only inhibit the release of inflammatory mediators, as confirmed herein, but also to suppress immune responses [16]. We thus speculate that, in addition to its ability to protect against the epithelial cell damages caused by toxin A, Peri-4 may also inhibit the mucosal immune cells responsible for the gut inflammation caused by this toxin A.…”
Section: Peri-4 Reduces Toxin A-induced Mucosal Damage and Inflammatisupporting
confidence: 60%
“…[14] The protective effect of Periplaneta americana extract on the function of the gastrointestinal mucosal barrier could be induced through the above-mentioned mechanism. A recent study [4] found that Periplaneta americana extract could reduce the level of endotoxin, thus protecting the function of the gastrointestinal mucosal barrier.…”
Section: Discussionmentioning
confidence: 99%
“…Effective medicine is expected to protect gastrointestinal mucosal barrier and reduce gastrointestinal complications. Studies [4,5] have shown that periplaneta americana extract has a positive effect on the gastrointestinal mucosa. Since periplaneta americana extract has been used in early enteral nutrition patients with SIRS in our hospitals, the present study was to determine whether it is effective in improving immune function, nutrition status and gastrointestinal complications.…”
Section: Introductionmentioning
confidence: 99%
“…The compounds were tested against various cancer cell lines and compounds 72 -- 74 showed significant cytotoxic activities against human liver (HepG2) and breast cancer (MCF-7) cells. In a small scale clinical study, sixty septic patients were treated with P. americana extract which successfully improved the condition and prognosis in patients with sepsis 129 .
Figure 12Structures of isocoumarins periplatins isolated from Periplaneta americana .
…”
Section: Blattodea (Cockroaches and Termites)mentioning
confidence: 99%